Gamification as a talent management tool in public sector education – a case study of cyber security simulation game (Academic Journal of Internal Affairs, 2021)
The latest techno-economic paradigm shift has brought the age of information and telecommunications. Tendency of growing digitalization implies related security risks. According to the latest predictions there will be approximately 3,5 million unfilled cybersecurity jobs worldwide by 2021. These open possibilities in the labour market have been appearing not only in the technical, but also in the strategic and public policy area. The Triple Helix Model, which presents innovation as a non-linear process, can present this technology developmentbased lack of human capacities as a network and collaboration possibility of universities, state, and industry. In one hand this is based on the nature of relevant knowledge of the given field, and on the constantly changing need of the industry, on the other hand higher education entering requirements and secondary education orientation belong to the state. This paper examines a simulation game organized in cooperation of all three actors, and to which motivated students – besides of university studies – can apply to gain extra knowledge and to take part in a competition. Developing from wargames these simulation games help students to gain not only professional knowledge but to develop in soft skills, too. The methodology is based on literature summary, questionaries, and interviews, conducted among students of the University of Public Service (Hungary) who took part in the ‘Cyber Security Simulation 2019 - Fix the System’ challenge. Results show that conscious carrier orientation of most students were strengthen. Satisfaction of both individual and group performance was clear, although many highlighted groupwork as the weakest point of their accomplishment, which must be developed further in the future. Students also emphasized that they gained professional knowledge, learned about decision making tools and developed soft skills such as ability for quick reaction or crisis communication. In one hand participants highlighted that these skills are important in their development, therefore stronger implementation of them could be a good path for university education. On the other hand, simulation games are thought to be a good challenge opportunity for the most motivated students outside of formal education to experience the flow.
Keywords: gamification; cyber security; talent management; education